2015
DOI: 10.1519/jsc.0000000000001025
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Aerobic and Strength Influences on Military Physical Readiness

Abstract: Physical fitness training of military recruits is an enduring focus of armies. This is important for safe and effective performance of general tasks that anyone may have to perform in a military setting as well as preparation for more specialized training in specific job specialties. Decades of studies on occupationally specific physical requirements have characterized the dual aerobic and strength demands of typical military tasks; however, scientifically founded strategies to prepare recruits with a good mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 77 publications
2
51
0
9
Order By: Relevance
“…Briefly, this test involves completing three workloads of 3-6 min at approximately 55, 65 and 75% of age predicted maximum heart rate (220 bpm -age in years) on a cycle ergometer (Monark, Monark Exercise AB, Varnsbro, Sweden), which was used as a method of prescribing a bout of individualised moderate intensity physical activity. This validation study was part of a larger project our team was conducting with Army personnel, so we decided to focus on an intensity that was most representative of typical training scenarios (Friedl et al, 2012). Previous studies have reported increases in both salivary cortisol and α-amylase in response to a single bout of exercise (Strahler et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, this test involves completing three workloads of 3-6 min at approximately 55, 65 and 75% of age predicted maximum heart rate (220 bpm -age in years) on a cycle ergometer (Monark, Monark Exercise AB, Varnsbro, Sweden), which was used as a method of prescribing a bout of individualised moderate intensity physical activity. This validation study was part of a larger project our team was conducting with Army personnel, so we decided to focus on an intensity that was most representative of typical training scenarios (Friedl et al, 2012). Previous studies have reported increases in both salivary cortisol and α-amylase in response to a single bout of exercise (Strahler et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…However, military training in the field consists mainly of prolonged aerobic physical activity with low training intensities. This kind of daily activity could potentially interfere with both optimal muscle strength and maximal aerobic capacity development (Friedl et al, 2015). Despite this, it is still quite uncommon to have structured and periodized training programs for optimal muscular strength and endurance development during military training (Szivak & Kraemer, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, military duties require more physical fitness than in the past (Friedl et al, 2015; Knapik, Reynolds, & Harman, 2004). In recruits, military training involves a high amount of physical activity, which can be a new experience for most of the recruits.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations